Breaking the barrier: an osmium photosensitizer with unprecedented hypoxic phototoxicity for real world photodynamic therapy. Issue 36 (26th August 2020) - Roque, John A.; Barrett, Patrick C.; Cole, Houston D.; Lifshits, Liubov M.; Shi, Ge; Monro, Susan; von Dohlen, David; Kim, Susy; Russo, Nino; Deep, Gagan; Cameron, Colin G.; Alberto, Marta E.; et al.
Abstract : A nontoxic Os(ii ) oligothienyl complex Os-4T is an extremely potent light-responsive anticancer agent that can be activated in hypoxia and with NIR light. Abstract : Hypoxia presents a two-fold challenge in the treatment of cancer, as low oxygen conditions induce biological changes that make malignant tissues simultaneously more aggressive and less susceptible to standard chemotherapy. This paper reports the first metal-based photosensitizer that approaches the ideal properties for a phototherapy agent. The Os(phen)2 -based scaffold was combined with a series of IP- n T ligands, where phen = 1, 10-phenanthroline and IP- n T = imidazo[4, 5- f ][1, 10]phenanthroline tethered to n = 0–4 thiophene rings. Os-4T ( n = 4) emerged as the most promising complex in the series, with picomolar activity and a phototherapeutic index (PI) exceeding 10 6 in normoxia. The photosensitizer exhibited an unprecedented PI > 90 (EC50 = 0.651 μM) in hypoxia (1% O2 ) with visible and green light, and a PI > 70 with red light. Os-4T was also active with 733 nm near-infrared light (EC50 = 0.803 μM, PI = 77) under normoxia. Both computation and spectroscopic studies confirmed a switch in the nature of the lowest-lying triplet excited state from triplet metal-to-ligand charge transfer ( 3 MLCT) to intraligand charge transfer ( 3 ILCT) at n = 3, with a lower energy and longer lifetime for n = 4. All compounds in the series were relatively nontoxic in the dark but became increasingly phototoxic with additional thiophenes. These normoxic and hypoxic activities are the largest reported to date, demonstrating the utility of osmium for phototherapy applications. Moreover, Os-4T had a maximum tolerated dose (MTD) in mice that was >200 mg kg −1, which positions this photosensitizer as an excellent candidate for in vivo applications.